The Effectiveness of Therapy Zikir in Reducing Anxiety Levels in Patients at RSU Lirboyo Kediri - Hafil, Ach. Shodiqil; Ningrum, Utari Prima (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
People who are sick with certain diagnoses tend to experience anxiety disorders. Anxiety is a psychological problem that has a negative impact on the patient, one of which will affect the healing process. Anxiety cannot be observed and seen directly. Alternative actions that can support the healing process are by providing spiritual treatment. Treatment with spiritual aspects, one of which is the provision of Zikir therapy which has a relaxing effect that can reduce anxiety levels in patients. This study aims to determine the effectiveness of Zikir therapy to reduce anxiety levels in patients at RSU Lirboyo Kediri. This study used the Quasi-Experimental method, with data mining obtained based on filling out questionnaires, as well as interviews with inpatients, and also from observations at Lirboyo General Hospital. The subjects in the study were several hospitalized patients with different levels of anxiety. Measurement of anxiety levels using the Hamilton Anxiety Rating Scale (HARS) anxiety scale. From the results of the study showed, that by doing Zikir therapy for ±10-15 minutes there can be a decrease in anxiety levels in patients. This proves that Zikir therapy can effectively reduce anxiety levels in inpatients at Lirboyo Hospital. Zikir therapy can create a feeling of calm and tranquility in the soul. Zikir therapy is also a therapy for a person's anxiety when he gets problems, feels himself weak, has no support and help in the face of various pressures and dangers in life. This research is expected to be a source of information in order to improve health service efforts by implementing Zikir therapy, especially in patients who experience high levels of anxiety.